Polysaccharide polyelectrolyte multilayer coating on poly(ethylene terephthalate). Issue 8 (15th April 2016) - Pérez‐Álvarez, Leyre; Lizundia, Erlantz; del Hoyo, Sara; Sagasti, Ariane; Rubio, Leire Ruiz; Vilas, J Luis
Abstract : Stable polysaccharide multilayers of chitosan (CHI) and hyaluronic acid (HA) are successfully adsorbed onto hydrophobic poly(ethylene terephthalate) (PET) using layer‐by‐layer assembly after hydrolysis of PET with NaOH. Abstract: Surface modification of poly(ethylene terephthalate) (PET) film was conducted by surface hydrolysis with NaOH and layer‐by‐layer assembly based on the electrostatic adsorption of oppositely charged polysaccharides: chitosan and hyaluronic acid. Hydrolysis of PET was verified by water contact angle variation of obtained surfaces and quantified using the toluidine blue O colorimetric method. Polysaccharide coatings of ca 200 nm could be observed using transmission electron microscopy for 10 chitosan/hyaluronic acid layers on PET film. Layer growth and degradation were easily monitored using UV‐visible spectroscopy after labelling of chitosan with fluorescein isothiocyanate of (FITC). Evaluation of degradation of the multilayers by FITC–chitosan release in phosphate buffer solution at pH = 7.4 showed that multilayers remain stable in phosphate buffer during the first 14 days after the loss of weakly bound polyelectrolytes. This fact makes the prepared polyelectrolyte multilayers interesting candidates to be employed as potential antibacterial implants and indwelling biomedical devices. © 2016 Society of Chemical Industry